Catalyzing voluntary pro-environmental behavior in the textile industry: environmentally specific servant leadership, psychological empowerment and organizational identity - Zafar, Hina; Jo, Ann Ho; Cheah, Jun-Hwa; Mohamed, Rosmah (Elsevier, 2022)
The demand for textile products worldwide has risen as people become increasingly fashion conscious. But looking fashionable causes detrimental effects to the environment as the textile industry is one of the most polluting industries in the world. While the textile industry plays a major role in Pakistan's economy, the industry is also a major cause of pollution for the country. This study examined the role played by environmentally specific servant leaders as a catalyst in creating a green organizational climate and fostering the organizational identity of employees. The findings also illuminate the psychological mechanism that connects a green organizational climate to voluntary pro-environmental behavior under high psychological empowerment. A two-wave study was conducted to collect data from the textile industry employees of Pakistan. Data from the sample of 109 managers and 459 employees revealed that environmentally specific servant leaders triggered the employees' voluntary pro-environmental behavior. Further, environmentally specific servant leadership was positively associated with voluntary pro-environmental behavior through organizational identity. The research supports the serial mediation of green organizational climate and organizational identity in provoking voluntary pro-environmental behavior. Psychological empowerment was also a significant moderator in the environmentally specific servant leadership-voluntary pro-environmental behavior relationship providing support for the collaborative effect of psychological empowerment and a green organizational climate in enhancing organizational identity. The implications for theory and practice are discussed within the context of the textile industry of Pakistan.